Analysis of selected cases of falls of hospitalized patients - Brabcová, Iva; Hajduchová, Hana; Tóthová, Valérie; Bártlová, Sylva; Filka, Jozef; Doseděl, Martin; Malý, Josef; Vlček, Jiří (Jihočeská univerzita v Českých Budějovicích, Zdravotně sociální fakulta, 2018)
Contemporary state: The falls of hospitalized patients are the most frequent adverse events in the hospital environment that prolong hospitalization and increase treatment costs. Goal: The goal of this study is to identify the causes and other factors causing falls regarding the selected group and recommend preventative and remedial measures. Materials and methods: It is a qualitative analysis of two casuistries of patients who fell during the hospitalization period. In both cases, we analyzed the root causes of falls (Root Cause Analysis). Results: In the first case, the cause of the fall was a sudden collapse of the patient, which resulted in the loss of balance. The collapse was caused by an infection, dehydration and the subsequent orthostatic hypotension. Other factors were the high-risk time (early morning) and insufficient bathroom lighting. In the second case, the fall was caused by the patient’s loss of balance during their morning hygiene regime. In both cases, the subsidiary factors were high age (80+), polymorbidity and pharmacotherapy. Conclusions: Falls, especially in elderly patients, are multifactorial. Preventative and remedial measures should be complex. In both cases, it is necessary to carry out the nursing plan with regards to the current changes in the health condition of hospitalized patients, and to share information on such changes among medical workers.
Keywords: Analysis; selected; cases; falls; hospitalized; patients